2007
DOI: 10.1021/om700603d
|View full text |Cite
|
Sign up to set email alerts
|

Cyclometalated and Alkoxyphenyl-Substituted Palladium Imidazolin-2-ylidene Complexes. Synthetic, Structural, and Catalytic Studies

Abstract: Some new N, N′-bis(aryl)imidazolinium salts (3a-h), in which the N-aryl groups have one unsubstituted ortho position and alkyl (Me, Pr i ) or alkoxy (OMe, OPr i ) substitution at the other ortho and/or para positions, have been prepared. They were used for the synthesis of N-heterocyclic carbene complexes of palladium in which the N-heterocyclic carbene is attached to cyclometalated or electron-rich aromatic rings (4, 5, 11d,e). The reaction of Pd(tmed)(CH 3 ) 2 with the N-heterocyclic carbene generated from 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(34 citation statements)
references
References 53 publications
3
31
0
Order By: Relevance
“…This compound is also notable, mainly for two reasons:1)itisthe first speciescontaining adianionic C,C,C-pincer ligand in the osmiumc hemistry [18] and 2) the orthometalation of both phenyl substituents has no precedentf or N,N'-diphenylbenzimidazolium and only once has been reported for N,N'-(diaryl)imidazolium counterparts. [19] Furthermore, it demonstratest he versatility of the NHC ligand, which can stabilizeh ighly unsaturated species by means of agostici nteractions and can act as neutral monodentate, [20] monoanionic chelate, [21] and dianionic pincert hrough reversible CÀHb ondactivations of the phenylg roups.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…This compound is also notable, mainly for two reasons:1)itisthe first speciescontaining adianionic C,C,C-pincer ligand in the osmiumc hemistry [18] and 2) the orthometalation of both phenyl substituents has no precedentf or N,N'-diphenylbenzimidazolium and only once has been reported for N,N'-(diaryl)imidazolium counterparts. [19] Furthermore, it demonstratest he versatility of the NHC ligand, which can stabilizeh ighly unsaturated species by means of agostici nteractions and can act as neutral monodentate, [20] monoanionic chelate, [21] and dianionic pincert hrough reversible CÀHb ondactivations of the phenylg roups.…”
mentioning
confidence: 93%
“…The geometry aroundt he osmium atom of 6 can be described as ad istorted trigonal bipyramidw ith apical phosphines and inequivalent angles of 76.5(3)8 (C-Os-C), 120.62 (18)8 (Cl-Os-C aryl ) and 162.87 (19)8 (Cl-Os-C BIm )w ithin the Y-shaped equatorial plane.…”
mentioning
confidence: 99%
“…Cyclometallation 21 of NHC ligands has been reported many times, but to the best of our knowledge none of these examples are cycloplatinated complexes. By contrast, a search of the Cambridge Crystallographic Database 22 reveals fiftyeight structurally characterised cyclopalladated NHC complexes; it is of relevance to note that none of these complexes have a three or four membered cyclometallated ring, only six 23,24 have a five membered ring, forty-two have a six membered ring, twelve a seven membered ring and eight an eight membered ring.…”
Section: Introductionmentioning
confidence: 99%
“…Ever since, the first cyclometalated complex was synthesized [13], cyclometalation has become an important part of organometallic chemistry and several reviews covering the subject have appeared [14][15][16]. The intramolecular activation of aromatic C-H bonds of coordinated ligands by transition metals represents an active area of research due to their applications, such as their use in regiospecific organic and organometallic synthesis, catalysis [17][18][19], photochemistry [20,21], the synthesis of new metal mesogenic compounds [22] and as potential biologically active materials [23,24]. Bhattacharya et al, reported the reaction of benzaldehyde thiosemicarbazone ligands with ruthenium(II) and 0022-328X/$ -see front matter Ó 2009 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%